Can we predict allergen‐induced asthma in patients with allergic rhinitis?. Issue 12 (December 2014) - Buslau, A.; Voss, S.; Herrmann, E.; Schubert, R.; Zielen, S.; Schulze, J.
Summary Background A high percentage of patients with allergic rhinitis (AR) exhibit signs of bronchial hyperreactivity (BHR), and approximately 30% may develop asthma later in life. Objective The aim of this study was to identify predictors for allergen‐induced asthma in patients with AR. Methods Hundred patients with AR selected by public posting and 20 healthy controls were enrolled. Twenty‐three patients with concomitant physician‐diagnosed asthma and four with a negative allergy test were excluded from further analysis. The remaining 73 subjects with AR underwent bronchial allergen provocation (BAP), which is considered the gold standard for the diagnosis of clinically relevant allergen‐specific asthma. The following parameters were measured to explore predictors for an early and late asthmatic response (EAR and LAR): standardised questionnaire, skin prick test (SPT), total IgE, specific IgE to grass pollen, FEV1, PD20FEV1 methacholine, exhaled nitric oxide (eNO) and eosinophils. Results Early asthmatic reaction was equally distributed between patients with and without signs of possible asthma by questionnaire (56.8% vs. 48.3%). The following cut‐off values showed the best combination of sensitivity and specificity for an EAR: specific IgE grass pollen 18.5 kU/L (AUC 0.83), SPT 8.5 mm (AUC 0.76), total IgE 95.5 kU/L (AUC 0.73), FEV1 102.4% (AUC 0.69), PD20FEV1 methacholine 1.67 mg (AUC 0.74), eNO 18.05 ppB (AUC 0.64) and eosinophils 115/mm3 (AUC 0.58). Conclusions and Clinical Relevance There is a considerable discordance between reported asthma signs and diagnosed disease by BAP. Simple measurement of allergen‐specific IgE for grass pollen was the best predictor of allergen‐induced asthma in patients with AR.